Women's Rights are Human Rights. To What Extent Does a Country's Feminist Foreign Policy Influence Development Assistance? - Sielker,Neele (2024)
This paper examines the influence of feminist foreign policy (FFP) on official development assistance (ODA) targeting gender equality and women’s empowerment in Canada, France, Germany, Luxembourg, the Netherlands, Spain, and Sweden. A growing number of governments worldwide have adopted FFP in contextually relevant ways, but previous research treats FFP and ODA as two separate concepts. This paper fills the gap in existing research by analyzing the relationship between the two. By combining content and descriptive data analysis, this paper provides a comprehensive understanding of how FFPs influence development assistance. The results show an overall increase in ODA for gender equality and women’s empowerment from 2002 to 2022, and that ODA with a significant objective is consistently higher than ODA with a principal objective. In 2023, Luxembourg, Germany and Sweden were the only countries to meet the 0.7 percent ODA/GNI target set by the United Nations. Spain and the Netherlands are the most supportive of women’s rights organizations and movements, although funding varies from year to year, and smaller, less institutionalized organizations remain underfunded agents of transformative change. Canada and France show that the adoption of FFP leads them to spend more on ODA than before the adoption of FFP, while the other countries do not show similar increases. The findings are limited because FFP is a relatively new policy concept, making it difficult to assess the influence of FFP on ODA. However, this paper provides an entry point for future research on the contextual adoption of FFP and its specific influence, particularly in the realm of development assistance.
Keywords: feminist foreign policy; development assistance; gender equality; intersectionality